Ecology of Microfungi in Mangrove Sediments at the Ganges River Estuary in India - Sengupta, Anjan; Chaudhuri, Subhendu (Indian Forester, 1995)
Population values of micro fungi in plant associated sediments of the four successional stages of mangrove vegetation at the Ganges river estuary in India showed an apparent inverse relationship with the levels of soil-water salinity. The highly saline formative and developed mangrove swamps had higher proportional population of more halotolerant fungi. Thirty eight species of filamentous fungi belonging to fourteen genera, with predominance of Aspergillus and Penicillium spp., were isolated from these sediments where species diversity was reduced with increasing concentrations of soil-water salinity. The fungi isolated varied in their nature and extent of halotolerance, with a few tolerating upto 15% in-vitro NaCl concentration. Leaves, roots and pneumatophores of Avicennia officinalis showed association of fungi similar in quality and diversity to that observed for sediments. Results established the presence of some ecologically adapted common decomposer species of microfungi in soil and plant association in the ecosystem which might have some role in detritus decomposition there.